Antioxidant activity of raw and extracts of heterotrigona itama honey from two different regions - Abdul Rahman, Fatin Nabilah (2017)
The growing interest in honey produced by Heterotrigona itama is mainly due to the contribution of its composition to many health benefits, such as the antioxidant potential of its phytochemical compound. The total phenolic and flavonoids content in Heterotrigona itama honey were studied by using a modified Folin-Ciocalteu method and aluminium chloride colorimetric assay. Different contribution of the entire honey and the phenolic extracted samples on their antioxidant activities were also studied on Heterotrigona itama honey from different site and time of collection. The total phenolic and flavonoid content of raw and phenolic extracted samples were statistically different with P < 0.05. The differences may be caused by the absence of sugar and insoluble matters that are able to affect the absorbance readings in the phenolic extracted sample. There was also significant difference between the total phenolic and flavonoid content of Heterotrigona itama honey collected from Kelantan and Terengganu. This was due to different chemical content in the different batches of Heterotrigona itama honey which contributes to different colour intensity.